A revised mechanism of action of hyperaldosteronism‐linked mutations in cytosolic domains of GIRK4 (KCNJ5). (17th January 2022) - Shalomov, Boris; Handklo‐Jamal, Reem; Reddy, Haritha P.; Theodor, Neta; Bera, Amal K.; Dascal, Nathan
Abstract : Abstract: G protein‐gated, inwardly rectifying potassium channels (GIRK) mediate inhibitory transmission in brain and heart, and are present in the adrenal cortex. GIRK4 ( KCNJ5 ) subunits are abundant in the heart and adrenal cortex. Multiple mutations of KCNJ5 cause primary aldosteronism (PA). Mutations in the pore region of GIRK4 cause loss of K + selectivity, Na + influx and depolarization of zona glomerulosa cells followed by hypersecretion of aldosterone. The concept of selectivity loss has been extended to mutations in cytosolic domains of GIRK4 channels, remote from the pore. We expressed aldosteronism‐linked GIRK4R52H, GIRK4E246K and GIRK4G247R mutants in Xenopus oocytes. Whole‐cell currents of heterotetrameric GIRK1/4R52H and GIRK1/4E246K channels were greatly reduced compared with GIRK1/4WT . Nevertheless, all heterotetrameric mutants retained full K + selectivity and inward rectification. When expressed as homotetramers, only GIRK4WT, but none of the mutants, produced whole‐cell currents. Confocal imaging, single‐channel and Förster Resonance Energy Transfer (FRET) analyses showed: (1) reduction of membrane abundance of all mutated channels, especially as homotetramers, (2) impaired interaction with Gβγ subunits, and (3) reduced open probability of GIRK1/4R52H . VU0529331, a GIRK4 opener, activated homotetrameric GIRK4G247R channels, but not GIRK4R52H or GIRK4E246K . In the human adrenocortical carcinoma cell line (HAC15), VU0529331 and overexpression of heterotetrameric GIRK1/4WT, but not overexpression of GIRK1/4 mutants, reduced aldosterone secretion. Our results suggest that, contrary to pore mutants of GIRK4, non‐pore mutants R52H and E246K mutants are loss‐of‐function rather than gain‐of‐function/selectivity‐loss mutants. Hence, GIRK4 openers may be a potential course of treatment for patients with cytosolic N‐ and C‐terminal mutations. Key points: Mutations in GIRK4 ( KCNJ5 ) G protein‐gated channels cause primary aldosteronism, a major cause of secondary hypertension. The primary mechanism is believed to be loss of K + selectivity. R52H and E246K, aldosteronism‐causing mutations in cytosolic N‐ and C‐ termini of GIRK4, were reported to cause loss of K + selectivity. We show that R52H, E246K and G247R mutations render homotetrameric GIRK channels non‐functional. In heterotetrameric context with GIRK1, these mutations impair membrane expression, interaction with Gβγ and open probability, but do not alter K + selectivity or inward rectification. In the human aldosterone‐secreting cell line, a GIRK4 opener and overexpression of heterotetrameric GIRK1/4WT, but not overexpression of GIRK1/4 mutants, reduced aldosterone secretion. Aldosteronism‐causing mutations in the cytosolic domain of GIRK4 are loss‐of‐function mutations rather than gain‐of‐function, selectivity‐loss mutations. Deciphering of exact biophysical mechanism that impairs the channel is crucial for setting the course of treatment. Abstract : Abstract figure legend There are two mutation types in KCNJ5 (GIRK4) that can cause excessive secretion of aldosterone, leading to primary aldosteronism. Mutations of the first type render the channel non‐selective to monovalent cations and often constitutively active, thus depolarizing the zona granulosa cells. This previously described mechanism underlies the disease‐causing effects of mutations of amino acid residues located in the pore region (red colour). Blockers of the channel may be useful as potential treatment to reduce aldosterone secretion. Here we show that mutations of the second type, located in the cytosolic domain remote from the pore, act by a different mechanism. They do not alter the channel's ion selectivity or rectification but cause poor expression or poor activation by Gβγ, resulting in a reduction in the cell's K + conductance and depolarization. In this case, GIRK4 openers can potentially be useful to prevent the excessive aldosterone secretion.